500.05 Comparison Between Fractional Flow Reserve (FFR) vs. Computational Fractional Flow Reserve Derived from Three-dimensional Intravascular Ultrasound (IVUSFR) and Quantitative Flow Ratio (QFR) - Kajita, Alexandre (2019)
BACKGROUND The determination of the ischemic status of a coronary artery by wireless physiologic assessment derived from angiography has been validated and approved in the US. However, the use ofplain angiography quantitative variables does not add much to thephysiology data since it has low correlation with fractional flowreserve (FFR) and predicts clinical outcomes poorly. Recently, a grayscale intravascular ultrasound (IVUS) derived physiology method(IVUSFR) was developed and showed a good correlation with invasiveFFR by combining the geometric advantages of IVUS with physiology.The aim of this study is to assess the coefficient of correlation (R) ofinvasive FFR compared to IVUSFR and quantitative flow ratio (QFR).METHODS Stable coronary artery disease (CAD) patients with intermediate lesions (i.e. 40?80% of diameter stenosis) were assessed by angiography and IVUS. QFR was derived from the angiography images, andIVUSFR was derived from quantitative IVUS data using computationalfluid dynamics. Coefficient of correlation (R) was used in this report.RESULTS Twenty-four patients with 34 lesions were included in theanalysis. The IVUSFR, invasive FFR, Vessel QFR fixed flow (vQFRf),and Vessel QFR contrast flow (vQFRc) values varied from 0.52 to 1.00,0.71 to 0.99, 0.55 to 1.00, and 0.34 to 1.00, respectively. The coefficient of correlation (R) of FFR vs. IVUSFR was 0.79; FFR vs. vQFRf was0.72; FFR vs. vQFRc was 0.65 (Figure).CONCLUSION Compared to invasive FFR, IVUSFR and vQFRf showed asimilar coefficient of correlation and were better than vQFR contrast flow